Mashlahah Married Pregnant Perspective Article 53 Compilation of Islamic Law - Ibnu Amin; Faisal Efendi; Hertasmaldi Hertasmaldi (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study aims to see how Mashlahah Based on Syara' and the (KHI) regarding the marriage of pregnant women out of wedlock. In this modern era, many women are pregnant even though they are not married. Islam provides all provisions for the benefit of mankind, so its teachings are called Salih likulli Zaman wa Makan. In Mashlahah Based on Syara' (Mashlahah Mu'tabarah, Mulgah, Mursalah) and Article 53 of the KHI indicate that this is a means to maintain the honor of women and their families after an opportunity that damages honor, namely pregnancy out of wedlock. This is also reinforced by the closeness of marriage without having to wait for the birth of a child in the womb. Based on the description above, it can be seen that the benefits listed in Article 53 of the KHI tend to be related to human interests to eliminate difficulties or narrowness that befall humans. Mashlahah seen from KHI regarding women who are married pregnant is the protection of lineage rights. Protection of honor, pregnant women out of wedlock who do not immediately marry the person who impregnated her will have an impact on the loss of honor for herself and her family.